Exhaled Carbon Monoxide Levels of Scavengers in Bantar Gebang Landfill, Bekasi - Agus Dwi Susanto; Dita Kurnia Sanie; Fahrial Harahap (Faculty of Medicine Universitas Airlangga, 2020)
Background: Scavengers in landfills have high risk to pollution exposure. Carbon monoxide (CO) is one of important pollutants produced by burning process. Exhaled CO levels in scavengers is predicted to increase, caused by pollution exposure in workplace area. There has been no data on exhaled CO levels in scavengers, especially in Bantar Gebang, Bekasi.Methods: This study used cross-sectional design to the scavengers who work and live in Ciketing Udik, Bantar Gebang, Bekasi. This study was conducted in January - March 2015, by doing interviews and giving questionnaires, and conducted exhaled CO test.Results: Total sample was 108 subjects. Exhaled CO test result was 46 subjects (42.6%) had exhaled CO 5-10 ppm, 36 subjects (33.3%) > 10 ppm, and 26 subjects (24.1%) ≤ 4 ppm. Multivariate analysis between exhaled CO levels with characteristics of the subjects found smoking habits were significantly correlated with CO exhalation levels (p=0,000).Conclusion: There were 33.3% scavengers who had exhaled CO > 10 ppm. Smoking habits were the only factor that significantly correlated with CO in scavengers’ exhalation.